The effects of saponin from Sapindus rarak fruit on rumen microbes and performance of sheep - Thalib, Amlius; Widiawati, Y; Hamid, H; Suherman, D; Sabrani, M (Indonesian Animal Sciences Society, 1996)
Eighteen local sheep weighing approximately 15 kg were randomly divided into 3 treatment groups . All animals received a mixture of elephant and native grasses (50 :50) ad libitum + concentrate (0.5% of liveweight) . The treatments given were : (1) no additive, (II) addition of placebo and (III) addition of methanol-extracted Sapindus rarak fruit (MES) at level of 0.07% of liveweight. Placebo and MES were given orally every 3 days . Feeding treatments were conducted for 14 weeks . Rumen liquor of all animals were collected in the third week